A fandom framework: critical digital media literacy in first-year composition curriculum - Wigginton, Brook, author; Amidon, Timothy R., advisor; Szymanski, Erika, committee member; Diffrient, David Scott, committee member (Colorado State University. Libraries, 2023)
Critical digital media literacy is an important factor in everyday life and in academia, but it has failed to gain momentum in first-year writing studies as a necessary literacy for students to develop. A comparative analysis of two first-year composition programs and the inclusion of autoethnographic examples is done to explore how critical digital media literacy is valued in current curriculum and to showcase its potential. Findings indicate that, while critical digital literacy is, in fact, a major part of first-year composition curriculum, it is not overtly named as such. The power in naming the literacies composition instructors expect students to enact and learn should not be underestimated, and composition scholars must renegotiate how we teach students to navigate our increasingly digitally mediated world. An example of how a fandom framework might name and develop those literacies is offered.